Parapharyngeal Space Tumors: The Infratemporal Fossa Approach - Shahinian, H. (1995)
Tumors of the parapharyngeal space, although mostly benign in their histopathology, present a challenge to the surgeon due to the limited access. Multiple approaches have been described in the literature for the extirpation of these tumors. The usual anatomic division of the parapharyngeal space into prestyloid and poststyloid spaces does not help the clinician determine which approach to use for a specific tumor. We have reviewed our 10-year experience at the University of Zurich. The usual presentation of the patients and the histopathologic characteristics of their tumors are compared. The radiological evaluation of these patients, their perioperative course, and complications are analyzed. The different surgical techniques used to treat the 72 patients in our series are described, with a special emphasis on the infratemporal fossa approach. Furthermore, a clinical division of the parapharyngeal space in the superior-inferior axis is established. The usefulness of this classification in helping the surgeon to decide which surgical approach is the most suitable for a particular lesion is discussed.